Cancer Screening in the Elderly: A Review of Breast, Colorectal, Lung, and Prostate Cancer Screening. Issue 4 (July 2017) - Kotwal, Ashwin A.; Schonberg, Mara A.
Abstract : Abstract: There are relatively limited data on outcomes of screening older adults for cancer; therefore, the decision to screen older adults requires balancing the potential harms of screening and follow-up diagnostic tests with the possibility of benefit. Harms of screening can be amplified in older and frail adults and include discomfort from undergoing the test itself, anxiety, potential complications from diagnostic procedures resulting from a false-positive test, false reassurance from a false-negative test, and overdiagnosis of tumors that are of no threat and may result in overtreatment. In this paper, we review the evidence and guidelines on breast, colorectal, lung and prostate cancer as applied to older adults. We also provide a general framework for approaching cancer screening in older adults by incorporating evidence-based guidelines, patient preferences, and patient life expectancy estimates into shared screening decisions.